225k views
4 votes
Determine the solution to the following system of equations: x + y = -3x - y = 1

(-2,3)
(-1,-2)
(0,0)
No Solution

User Dtorgo
by
4.6k points

1 Answer

4 votes

Answer:

( -1,-2)

Explanation:

x + y = -3

x - y = 1

Add the two equations together to eliminate y

x + y = -3

x - y = 1

------------------

2x = -2

Divide by 2

2x/2 = -2/2

x = -1

Now find y

x+y =-3

-1 +y = -3

-1+1 +y = -3+1

y = -2

( -1,-2)

User Alexandra Axt
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.